ANALISIS PERHITUNGAN DAN PELAPORAN PPH PASAL 21 PADA PT. SAMEROT TRI PUTRA - Warangkiran, Ridelson Y.S.; Morasa, Jenny; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2018)
Income tax Article 21 is tax on earnings in the form of wages, salaries, honorarium, benefits, and other payments by the name and in any form in connection with employment or Office, services, and activities performed by those Taxpayers persons in the country. On the basis that's then Government agencies or companies give salary to employees is obliged to apply the calculation and reporting of income tax Article 21 and received by employees correctly. This research was conducted on the company that is responsible for contracting i.e. PT. Samerot Tri Putra, the goal in this study was to analyze the calculation and reporting of income tax Article 21 carried out by PT. Samerot Tri Putra does were in accordance with Act No. 36 year 2008 about income tax. This research uses descriptive research methods with qualitative approaches. The results of this research show that the calculation and reporting of income tax Article 21 carried out by PT. Samerot Tri Putra has been in accordance with Act No. 36 year 2008 about income tax.Keywords: Analysis, Reporting, Income Tax Article 21